Characterization of Gonadotropin-Releasing Hormone (GnRH) Genes From Cartilaginous Fish: Evolutionary Perspectives - Gaillard, Anne-Laure; Tay, Boon-Hui; Pérez Sirkin, Daniela I.; Lafont, Anne-Gaëlle; De Flori, Céline; Vissio, Paula G.; Mazan, Sylvie; Dufour, Sylvie; Venkatesh, Byrappa; Tostivint, Hervé (Frontiers in Neuroscience, 2018)
The neuropeptide gonadotropin-releasing hormone (GnRH) plays an important role in the control of reproductive functions. Vertebrates possess multiple GnRH forms that are classified into three main groups, namely GnRH1, GnRH2 and GnRH3. In order to gain more insights into the GnRH gene family in vertebrates, we sought to identify which paralogs of this family are present in cartilaginous fish. For this purpose, we searched the genomes and/or transcriptomes of three representative species of this group, the small-spotted catshark, Scyliorhinus canicula, the whale shark, Rhincodon typus and the elephant shark Callorhinchus milii. In each species, we report the identification of three GnRH genes. In catshark and whale shark, phylogenetic and synteny analysis showed that these three genes correspond to GnRH1, GnRH2 and GnRH3. In both species, GnRH1 was found to encode a novel form of GnRH whose primary structure was determined as follows: QHWSFDLRPG. In elephant shark, the three genes correspond to GnRH1a and GnRH1b, two copies of the GnRH1 gene, plus GnRH2. 3D structure prediction of the chondrichthyan GnRH-associated peptides (GAPs) revealed that catshark GAP1, GAP2, and elephant shark GAP2 peptides exhibit a helix-loop-helix (HLH) structure. This structure observed for many osteichthyan GAP1 and GAP2, may convey GAP biological activity. This HLH structure could not be observed for elephant shark GAP1a and GAP1b. As for all other GAP3 described so far, no typical 3D HLH structure was observed for catshark nor whale shark GAP3. RT-PCR analysis revealed that GnRH1, GnRH2 and GnRH3 genes are differentially expressed in the catshark brain. GnRH1 mRNA appeared predominant in the diencephalon while GnRH2 and GnRH3 mRNAs seemed to be most abundant in the mesencephalon and telencephalon, respectively. Taken together, our results show that the GnRH gene repertoire of the vertebrate ancestor was entirely conserved in the chondrichthyan lineage but that the GnRH3 gene was probably lost in holocephali. They also suggest that the three GnRH neuronal systems previously described in bony vertebrates are also present in cartilaginous fish.